Hydrocolloid Dressing on Wound Healing in Patients with Diabetes Mellitus - Ade Tika Herawati; Dede Nuraziz Muslim (Sarana Ilmu Indonesia (salnesia), 2026)
Diabetes Mellitus (DM) was a chronic disease whose prevalence continues to increase globally, including in Indonesia. In West Java Province, based on data from the Health Office, the number of DM sufferers has increased significantly in recent years. DM patients in West Java experience complications ranging from 15% to 20%. In 2019, Sukabumi Regency recorded 148,447 DM sufferers, while Bandung Regency recorded 45,412 people. The purpose of this study was to determine the effectiveness of Hydrocolloid administration on wound healing. The method used was pre-experimental with pretest-posttest without a control group. The research subjects were DM patients with wounds who visited the nursing home. The sampling technique used was purposive sampling with inclusion and exclusion criteria. The instrument used was the Bates Jensen Wound Assessment Tools (BWAT) which was measured 4 times over 2 weeks. Wound healing data was analyzed using a statistical test: t-test to see the effectiveness of Hydrocolloid dressing wound healing. Results: p-value < 0.05 showed that the administration of Hydrocolloid was proven to be effective in healing wounds in Diabetes Mellitus patients. Suggestion: Seeing the effectiveness of Hydrocolloid dressing in Diabetes Mellitus patients, it was recommended for wound nurses to provide Hydrocolloid as a dressing on wounds to accelerate wound healing.